Skin temperature changes of muscle regions in training swimmers - Rybárová, S.; Novotný, J. (Journal of Human Sport & Exercise, 2015)
Our aim was to detect changes in infrared radiation, overloaded structures of the musculoskeletal system at the main part of the shoulder girdle and upper body with the help of elite swimmers of Kometa Brno. First measurement was done before training and second 15 minutes after training in water in the swimming pool. The group consisted of seven Czech national swimmers. Athletes participated in testing during six months. Every measurement contains four positions. Front and back side, right and left side. Every athlete went through 13 measurements. We directed infrared thermograph camera FlukeTiR at 10 muscular groups that are most used in swimming. Besides we have form about training with kilometres, other exercise out of water, competitions, illness and be absent at training and other pain muscles, ligaments etc. We have analysed all temperatures only of one swimmer. Here was significant increased temperature after swimming only in deltoideus anterior at right side (from 33,4±1,02°C to 34,0±0,69°C). The other temperature was significant decreased: muscles groups of pectoralis major and minor (right side from 33,6±0,92 to 33,1±0,61°C; left side from 33,8±0,82 to 33,1±0,69°C), latissimus dorsi and erector spinae - pars lumbalis at both sides together. Five of twenty muscle regions have notable tendencies of increased temperatures, including a front part of deltoideus at right side which is very active by spreading arm forward and beginning of swimming stroke. In nine areas, including the main agonist for swimmers movement forward - triceps brachii, we found out only no significant lowering of temperatures. That was caused by cooling of the swimmer in the water. We have next six swimmers to analysis.